Impact of Internal Factors on Banks Profitability In Pakistan - Tariq, Amna; Jeganathan, Lheela; Mariappan, Vickineswaran (Politeknik Ilmu Pemasyarakatan, 2023)
This paper investigated the internal factors that affecting profitability of banks in Pakistan. This study was used annual data of 19 banks of Pakistan from 2012 to 2016. Descriptive statistics and regression analysis are used to test the relationship between return on equity as dependent variable and independent variables. Capital adequacy, liquidity, bank size and expense management are used as independent variables and return on equity is used as dependent variable. The findings of this study showed that all the independent variables have a significant impact on profitability. Capital adequacy, bank size and expense management are variables which have positive and significant impact on the return on equity. Other variable liquidity has a negative but significant relationship with the return on equity. The results of the descriptive statistics show that liquidity and bank size have high mean values while the standard deviation has low values, but the other variables have low mean values.